Construction and validation of an educational technology on nutritional guidelines in chronic non-communicable diseases (Research, Society and Development, 2025)
The objective of this study is to present the process of construction and validation of an educational booklet on nutrition in chronic non-communicable diseases for Community Health Agents (CHA). Methodological research was carried out, of the validation type, with a quantitative approach. A Content Validity Index (CVI) equal to or greater than 0.80 was used as standard. The exact binomial distribution test was performed, considering p (probability) greater than 0.80 (80%). In this way, agreement was obtained between the judges, with a significance level of 5%. To validate the booklet, the Delphi technique was performed, with 11 judges selected, the majority of whom were nutritionists (45.4%), with a prevalence of females (90.9%). The booklet was composed in its post-validation with 52 pages. All pages were counted sequentially, however, the numbering in Arabic numerals began to be recorded only from the first textual page, in its lower right margin. The title font used on the cover was Bree Serif size 24 and 42, both in bold white, Arimo font size 32 for the information contained in the text and Bree Serif font size 60 in bold for all chapter titles. to the global CVI, which in the first round obtained 0.97, in the second round, a global CVI of 0.99 was obtained, and a p value > 0.80, validating the constructed digital booklet. It is believed that the validation of this educational technology for CHWs will facilitate the health education process, and consequently, provide health promotion actions.